Noncovalent Immobilization of Pentamethylcyclopentadienyl Iridium Complexes on Ordered Mesoporous Carbon for Electrocatalytic Water Oxidation. Issue 11 (15th November 2021) - Geer, Ana M.; Liu, Chang; Musgrave, Charles B.; Webber, Christopher; Johnson, Grayson; Zhou, Hua; Sun, Cheng-Jun; Dickie, Diane A.; Goddard, William A.; Zhang, Sen; Gunnoe, T. Brent
Abstract : Molecular Iridium Complexes for Electrocatalytic Water Oxidation In article number 2100037, Ana M. Geer, William A. Goddard III, Sen Zhang, T. Brent Gunnoe, and co‐workers report that iridium‐based solid‐state water oxidation anodes are prepared by immobilizing cyclopentadienyl iridium (III) complexes onto ordered mesoporous carbon via π‐stacking. The heterogenized molecular catalysts exhibit high turnover frequencies at low overpotentials for electrochemical water oxidation under the acidic conditions.